PENELITIAN AGAMA DAN KEAGAMAAN DI PERGUGURUAN TINGGI AGAMA ISLAM (PENDAIS, 2022)
This article aims to delinto the study of religion and religion in the islamic college. And pointing out that islamic religious colleges contribute to programs that are not centered on colleges, and that the quality of islamic education education in college plays a large part in the context of human development. But at the same time there was a challenge to overcome, and the development of islamic higher education was not only in state institutions but in private. College became not only a means of transforming knowledge but also a society's dynamitor. It employs qualitative research methods with a social religious approach. This paper is expected to contribute to the framework of theoretical and practical strategies in the development of science in science.Keywords: Religious education, Character, Students, Pradigma, Moderation.